Semantika teksta i makrostilistička analiza - Kovačević, Marina (Stylistyka, 1996)
Textual semantics is seen as a means of macrostylistic analysis. The problem of meaning and sense of a text is approached linguistically and extra-linguistically. At the linguistic level semantic factors within a text are being identified: the layout of a semantic field of a discourse (following the principles of metaphoric and metonymic structuring) is shown, * means of semantic cohesion are being pointed out, as well as points of semantic emphasis and various other means of structuring semantic emphasis. The sense is being approached in relation to what is being called the internal context and the external context. Nemir (Anxiety), a prose poem by Miroslav Krleža, is being analysed in this way, and the style is being defined as a relation between meaning (sense) and context.